Does intra-articular injection of antimicrobials alongside corticosteroids or other medications reduce the risk of synovial sepsis? - Braid, Helen R (Veterinary Evidence, 2019)
PICO question In horses, does treatment with intra-articular antimicrobials concurrently with intra-articular corticosteroids reduce the risk of iatrogenic synovial sepsis compared to intra-articular corticosteroids alone? Clinical bottom line From the current literature, there is no evidence showing that intra-articular injection of antibiotics in conjunction with corticosteroids reduces the risk of synovial sepsis. However, the intra-articular injection of polysulphated glycosaminoglycans (PSGAGs) in combination with corticosteroids was noted as a risk factor for developing iatrogenic synovial sepsis and therefore concurrent antibiotic injection when administering PSGAGs may be warranted. The reported frequency of infection following intra-articular injections was very low (0.02–0.08%). An overall prevalence of iatrogenic synovial sepsis following all intra-articular injections based on data from all included studies was calculated as 0.02% (CI 0.02–0.03%). However, due to the paucity of literature on the topic, further studies are required in this field to determine more accurate clinical recommendations.